2017
DOI: 10.1063/1.5000439
|View full text |Cite
|
Sign up to set email alerts
|

Formation of soap bubbles by gas jet

Abstract: Soap bubbles can be easily generated by varies methods, while their formation process is complicated and still worth study. A model about the bubble formation process was proposed in Phys. Rev. Lett. 116, 077801 recently, and it was reported that the bubbles were formed when the gas blowing velocity was above one threshold. However, after repeating these experiments, we found the bubbles could be generated in two velocities ranges which corresponded to laminar and turbulent gas jet respectively, and the predic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…Interestingly Zhou et al, 19 using an experimental setup similar to Salkin's, have observed the opposite of our findings: smaller bubbles at lower air speeds, larger at higher speeds and a regime between in which no bubbles are observed. However, their air speeds (as characterised by the Reynolds number) are slower than ours, meaning that their no-bubble regime may correspond with our almost closed bubbles regime.…”
Section: Dripping Modecontrasting
confidence: 98%
“…Interestingly Zhou et al, 19 using an experimental setup similar to Salkin's, have observed the opposite of our findings: smaller bubbles at lower air speeds, larger at higher speeds and a regime between in which no bubbles are observed. However, their air speeds (as characterised by the Reynolds number) are slower than ours, meaning that their no-bubble regime may correspond with our almost closed bubbles regime.…”
Section: Dripping Modecontrasting
confidence: 98%
“…For example, Huibers & Shah (1997) determined the thickness of the soap film by using the multispectral method and found that the thickness of the soap film varied over four orders of magnitude, from less than 5 nm to greater than 50 μm, depending on the spectral range and accuracy of the spectrophotometer. Quantitative analysis on the conditions, criteria and main features of soap bubble formation has been extensively performed recently, both experimentally and theoretically (Dong et al 2014;Panizza & Courbin 2016;Salkin et al 2016;Davidson & Ryu 2017;Zhou et al 2017), while creation of soap bubbles through various methods has also received attention. For example, Frazier, Jiang, & Burton (2020) highlighted the process of making giant bubbles, while Zang et al (2018) generated bubbles from droplets using ultrasound resonance.…”
Section: Introductionmentioning
confidence: 99%